2013
DOI: 10.1002/gea.21450
|View full text |Cite
|
Sign up to set email alerts
|

Raw Materials for Archaeological Pottery from the Campania Region of Italy: A Petrophysical Characterization

Abstract: We performed petrophysical analyses on 34 clayey samples of different geological origin within the Campania region of Italy in order to determine possible sources of raw materials used to produce ancient pottery. Possible raw material sources can be grouped into high-CaO clays (HCC) and low-CaO clays (LCC). HCC are mainly represented by more recent (Miocene-Pleistocene) basinal sediments whereas LCC tend to be associated with basinal, alluvial, and pyroclastic deposits. A chemical comparison between clayey raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 40 publications
(50 reference statements)
5
54
0
1
Order By: Relevance
“…The Ischia activity is dominated by the emplacement of pyroclastic rocks, related to the caldera formation. The seaward ingression has permitted the sedimentation of clay deposits rich in quartz, carbonates (e.g., De Bonis et al, 2013) and microfossils (foraminifera, ostracoda; Barra et al, 1992). Mt.…”
Section: Sampling and Analytical Techniquesmentioning
confidence: 98%
“…The Ischia activity is dominated by the emplacement of pyroclastic rocks, related to the caldera formation. The seaward ingression has permitted the sedimentation of clay deposits rich in quartz, carbonates (e.g., De Bonis et al, 2013) and microfossils (foraminifera, ostracoda; Barra et al, 1992). Mt.…”
Section: Sampling and Analytical Techniquesmentioning
confidence: 98%
“…Hierarchical cluster analysis dendrogram (d) resulting from multivariate statistical analyses of chemical data. Clays from the Island of Ischia (IS 1, 2, 3, 5, 6) and the Argille Varicolori Formation (SQ1, TRE1; data from De Bonis et al, ) were also reported for comparison [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Results and Discussionmentioning
confidence: 99%
“…With respect to sources of clay, basinal sediments along with alluvial deposits and strongly weathered pyroclastic soils are exposed in the study area and farther inland (De Bonis et al, ). Basinal clays mainly crop out along the Apennine chain and are composed of clayey deposits of the lower Messinian Sicilide Unit ( Argille Varicolori ) and by the Mio‐Pliocene successions of the Pietraroja Formation (Bonardi, Ciarcia, Di Nocera, Montano, & Sgrosso, ).…”
Section: Brief Geological Remarksmentioning
confidence: 99%
See 2 more Smart Citations